CARDIAC SURGERYDo age, diabetes and left ventricular function affect the outcomes of ischemic mitral valve repair? - Jankauskiene, Loreta; Svagzdiene, Milda; Sirvinskas, Edmundas; Kinduris, Sarunas; Adomavicius, Darius (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : It is well documented that older age, chronic concomitant diseases (such as diabetes mellitus, chronic obstructive lung disease, etc.), and poor left ventricular function can increase the postoperative complication rate and worsen the general outcomes of coronary artery bypass (CABG) and concomitant repair of ischemic mitral regurgitation (MR). Material and methods : Retrospective data of 394 patients after CABG and mitral valve (MV) repair (mainly annuloplasty) were analyzed. Patients were grouped according to age, diabetes mellitus (DM), and left ventricular ejection fraction (LVEF). Echocardiography data, the rate of postoperative complications (cardiogenic shock, preoperative myocardial infarction, bleeding from the gastrointestinal tract, cognitive disorders, stroke, sepsis, deep wound infection), and early and late mortality were compared between paired groups. Results: There were no differences between age groups in reverse positive remodeling of LV. A significantly higher incidence of sepsis and deep wound infection in younger patients was observed. Patients with DM had no change in the pre-postoperative NYHA class and a higher rate of perioperative MI (10.3% vs. 3.1% respectively, p < 0.05) in comparison to patients with no DM. In all LVEF groups, MR was significantly decreased, but reverse positive remodeling of LV was pronounced only in those with “poor” and “moderately lowered” LVEF. Postoperative complications did not differ among these three groups. Conclusions : Elderly age, concomitant DM and lowered LVEF do not influence either early or late mortality, including early postoperative outcomes after MV repair for ischemic MR following CABG. Concomitant DM increases the rate of perioperative MI and impairs reverse remodeling of LV.